Analysis and Research on the Centimeter Band Receiver Amplitude Calibration Method - Kai Wang; Maozheng Chen; Jun Ma; Xuefeng Duan; Yang Wang; Liang Cao; Hao Yan; Binbin Xiang (Advances in Astronomy, 2020)
The receiver is a signal receiving device in a radio telescope system. As an important parameter to characterize the receiver performance, noise temperature is very practical to calibrate accurately. The traditional receiver noise temperature calibration method is the cold and ambient load method. Through the establishment of K-band ambient receiver, and its amplitude calibration test platform of the cold and ambient load method, chopper wheel method, and ambient and hot load method, comparison and analysis of the above three methods were carried out. The test and calculation results show that the test accuracy of the cold and ambient load method is about 1.3%, that of the chopper wheel method (nonlow elevation) is about 3%, and that of the ambient and hot load method is about 9%. The test accuracy of the ambient and hot load method is slightly lower than that of the above two methods. The analysis is mainly due to the uncertainty of the hot load temperature and the small temperature difference between the two loads, which leads to the deterioration of the overall accuracy. But the advantage is that the method can perform real-time calibration in the process of observation, and it is easier to implement than the traditional cold and ambient load method. The results of noise temperature measurement are compared with those of theoretical calculation, the error is basically within 10%, and it can satisfy the demand of the noise temperature test. In the future, we expect that on the basis of increasing the hot load temperature, further experiments were carried out on the thermostatic treatment of hot load and the accuracy of temperature acquisition, and finally we hope that this method can better meet the testing requirements of receiver noise temperature and radio source amplitude calibration.